Supervised Cycling Training Improves Erythrocyte Rheology in Individuals With Peripheral Arterial Disease - Hsu, Chih-Chin; Lin, Yu-Ting; Fu, Tieh-Cheng; Huang, Shu-Chun; Lin, Cheng-Hsien; Wang, Jong-Shyan (Frontiers in Physiology, 2022)
Peripheral arterial disease (PAD) results in insufficient flow to lower extremities. Aerobic exercise provides health benefits for individuals with PAD, but basic science behind it is still debated. Twenty-one PAD patients aged about 70 years with female/male as 7/14 were recruited. Among them, 11 were randomized to have supervised cycling training (SCT) and 10 to receive general health care (GHC) as controls. SCT participants completed 36 sessions of SCT at ventilation threshold within 12 weeks and the controls received GHC for 12 weeks. Ankle brachial index (ABI), 6-minute walk test (6MWT), peak oxygen consumption (VO2peak), minute ventilation (VE), minute carbon dioxide production (VCO2), erythrocyte rheology, including the maximal elongation index (EImax) and shear stress at 50% of maximal elongation (SS1/2), and the Short Form-36 (SF-36) questionnaire for quality of life (QoL) were assessed before and 12 weeks after initial visit. SCT significantly increased ABI, 6MWT distance, V ̇O2peak, SF-36 score, but depressed V ̇E/V ̇CO2 slope. The exercise regimen also depressed the SS1/2 and SS1/2-to-EImax ratio (SS1/2/EImax) but increased the erythrocyte osmolality in the hypertonic region corresponding to 50% of EImax and the area under EI–osmolality curve. However, no significant changes in aerobic capacity and erythrocyte rheological properties were observed after 12-week of GHC. In conclusion, SCT improves functional aerobic capacity, enhances erythrocyte membrane stability as well as osmotic deformability, and consequently promotes QoL in PAD patients.